77-3x=15x+17

Simple and best practice solution for 77-3x=15x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 77-3x=15x+17 equation:


Simplifying
77 + -3x = 15x + 17

Reorder the terms:
77 + -3x = 17 + 15x

Solving
77 + -3x = 17 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
77 + -3x + -15x = 17 + 15x + -15x

Combine like terms: -3x + -15x = -18x
77 + -18x = 17 + 15x + -15x

Combine like terms: 15x + -15x = 0
77 + -18x = 17 + 0
77 + -18x = 17

Add '-77' to each side of the equation.
77 + -77 + -18x = 17 + -77

Combine like terms: 77 + -77 = 0
0 + -18x = 17 + -77
-18x = 17 + -77

Combine like terms: 17 + -77 = -60
-18x = -60

Divide each side by '-18'.
x = 3.333333333

Simplifying
x = 3.333333333

See similar equations:

| b-2x=(-6)-2(6) | | (6x+1)+x=4x+19 | | 4x+9=-107-7x | | (2-a)(2-a)-4=0 | | x+.23=24.60 | | 3-2y=(3y-2)-5y | | 7q+11=102 | | 14=3d-15+2a-6 | | 13-7x=143-42x | | 8x-30=3x | | 12p=168 | | ln(x)+ln(x-9)=ln(22) | | -5x-9x=-84 | | .75t-4=5 | | 5.7+1.1n=2.62 | | -5(t-9)-(t+1)=9 | | 6x-11=10-51 | | 225-4x=41x+15 | | 11-10-x=175-38x | | 11-1-x=175-38x | | x^2+16x+53=0 | | x+2=30 | | 0.04x-78.64=1.6 | | 2x+30=5 | | 2(x+2)=30 | | 13-8x=128-43x | | (x^2)+6x+8=0 | | 4x^2-49y^2=0 | | 4x+38=13x+70 | | 4x+38=18x+70 | | (5/8)h=160 | | 32+x=120 |

Equations solver categories